A multidimensional typology of riverbank habitats explains the distribution of European grayling (Thymallus thymallus L.) fry in a temperate river. Issue 4 (26th November 2013) - Cattanéo, Franck; Grimardias, David; Carayon, Marie; Persat, Henri; Bardonnet, Agnès
Abstract For species at risk, rehabilitation of riverbank habitats may be a promising way to sustain abundance of early‐life stages, provided that fish—habitat relationships are significant and the scale at which they are described is relevant to both fish ecology and management purposes. Here, habitat use of the threatened European grayling (Thymallus thymallus) fry was analysed in an alluvial French‐Swiss border river, the Allondon. Based on five descriptive variables, a practical typology of available bank habitats was first defined to categorise ecological conditions into five easily distinguishable habitat types (HTs). These represent marginal patches of multivariate homogeneous habitat from a few to tens of square metres [median area = 8 m−2; range (10%–90%) = 1.9–32.6 m−2]. Comparing the habitat used by fry to those available revealed a clear selection for two of the five HTs, that is, gravel bar shorelines (HT4) and depositional beaches along pool margins (HT3). Because of their multidimensional nature and larger spatial scale, HTs did not strictly reflect an up‐scaling of univariate selection patterns at the microhabitat scale. Results emphasised that the preservation of the alluvial dynamics of the river and bank patchiness are basic to European grayling, and suggested that the patch scale may represent a good compromise between ecological relevancy and practical management needs. The herein developed typological approach may be transferred to other rivers and help conserve European grayling populations by enhancing fry habitat suitability.